Linkages between Financial Risk and Sustainability in the Banking Sector: A Bibliometric Study - Judijanto, Loso; Yusniar, Yusniar; Arini, Rani Eka (Westscience Press, 2024)
This paper presents a bibliometric analysis examining the evolution of research within the sustainability and risk management sectors in banking, based on several visual network analyses. Initial findings delineate thematic clusters focusing on green banking, financial performance, and the impact of technological advancements such as fintech. An investigation into the temporal progression of research themes from 2017 to 2021 highlights a significant shift from foundational concerns about financial stability to more nuanced discussions integrating sustainability and economic inclusivity. Additionally, the research identifies potential gaps in the literature, particularly around the integration of Islamic banking with green practices and the management of environmental and climate-related risks. Analysis of author collaborations within these thematic areas reveals a robust network of scholars, characterized by both dense, focused groupings and broader, interdisciplinary linkages. This study underscores the dynamic and evolving nature of academic discourse in sustainable finance, suggesting promising areas for future research.